How do humans value urban nature? Developing the perceived biophilic design scale (PBDs) for preference and emotion - Hung, Shih-Han; Chang, Chun-Yen (Urban forestry & urban greening, 2022)
With the growth of urbanization and the increasingly hectic pace of life, exposure to urban nature within blue-green infrastructure is greatly impacting human health and well-being. Biophilia, an evolutional concept, conveys the initial connection between humans and nature; biophilic design transfers into design attributes to indicate the relationship between humans and the environment. A significant advantage of experiencing nature is positive restoration; however, only limited research has been conducted on connecting biophilic design and mental health. This study adopted our perceived biophilic design items (PBDi) to examine the relationship between landscape preferences and emotional states in urban green spaces. Online surveys (valid total n = 477) examining these biophilic items, landscape preferences, and emotional states were conducted. Seven aspects—(1) evolved human–nature relationships, (2) place-based relationships, (3) visual aesthetic quality, (4) state of natural change, (5) environmental perception, (6) sense of compatibility in the built environment, and (7) natural form of design method —were confirmed through exploratory factor analysis (EFA), with 64.35 % of the cumulative variance, and confirmatory factor analysis (CFA) demonstrated good convergent validity and discriminant validity. The overall perceived biophilic design scale (PBDs) with 28 items had a Cronbach’s α of 0.91. In addition, it was found that PBDs significantly explained landscape preferences and positive emotional states within urban nature. The findings provide an alternative tool for measuring human biophilic perceptions that influence environmental experiences. In addition, each item in the scale could be used as a biophilic guideline for designers and planners to reinterpret nature in cities and to enhance our connection to nature in general. •We developed an alternative scale on humans perceived the environmental attributes.•Perceived Biophilic design positively predict landscape preference.•Perceived Biophilic design relates to positive and negative emotion.•Evidence-based on Biophilic in built environment.